Survival of patients with alcohol use disorders discharged from an emergency department: a population-based cohort study - Gunnarsdottir, Anna Steinunn (BMJ Open, 2014)
OBJECTIVES: The aim was to study the cause-specific mortality of users of the emergency department (ED) who received a diagnosis of alcohol use disorder (AUD) in comparison with mortality of other users of the department. DESIGN: A population-based prospective cohort study. PARTICIPANTS: All patients aged 18 years and above who were subsequently discharged home from the ED during the years 2002–2008. A total of 107 237 patients were followed by record linkage to a nationwide cause-of-death registry: 1210 patients with AUD as the main discharge diagnosis and 106 027 patients in the comparison group. HR and 95% CIs were calculated. SETTING: ED at Landspitali—the National University Hospital of Iceland, Reykjavik, Iceland. The hospital offers tertiary care and is the number one trauma centre and community hospital for the greater Reykjavik area. According to the population registry, 78% of the inhabitants of the area attended the ED during the study period. RESULTS: 72 patients died in the AUD group and 4807 in the comparison group. The adjusted HR for all causes of death was 1.91 (95% CI 1.51 to 2.42). The HR for AUDs was 47.68 (95% CI 11.56 to 196.59) while for alcohol liver disease the HR was 19.06 (95% CI 6.07 to 59.87). The HR was also elevated for diseases of the circulatory system: HR 2.52 (95% CI 1.73 to 3.68); accidental poisoning: HR=13.64, (95% CI 3.98 to 46.73); suicide: HR=2.72 (95% CI 1.08 to 6.83); and event of undetermined intent: HR=10.89 (95% CI 4.53 to 26.16). CONCLUSIONS: AUD as the discharge diagnosis at the ED, among patients who were not admitted to a hospital ward but discharged home, predicts increased mortality. As the results conclusively show the vulnerability of these patients, one can question whether their needs are adequately met at the ED.